White Matter Deterioration May Foreshadow Impairment of Emotional Valence Determination in Early-Stage Dementia of the Alzheimer Type - Rajmohan, Ravi; Anderson, Ronald C.; Fang, Dan; Meyer, Austin G.; Laengvejkal, Pavis; Julayanont, Parunyou; Hannabas, Greg; Linton, Kitten; Culberson, John; Khan, Hafiz M. R.; De Toledo, John; Reddy, P. Hemachandra; et al. (Frontiers in Aging Neuroscience, 2017)
In Alzheimer Disease (AD), non-verbal skills often remain intact for far longer than verbally mediated processes. Four (1 female, 3 male) participants with early-stage Clinically Diagnosed Dementia of the Alzheimer Type (CDDAT) and eight neurotypicals (NT) (4 females, 4 males) completed the emotional valence determination test (EVDT) while undergoing BOLD fMRI. We expected CDDAT participants to perform just as well as NTs on the EVDT, and to display increased activity within the bilateral amygdala and right anterior cingulate cortex (r-ACC). We hypothesized that such activity would reflect an increased reliance on these structures to compensate for on-going neuronal loss in frontoparietal regions due to the disease. We used DTI to determine if white matter damage had occurred in frontoparietal regions as well. CDDAT participants had similar behavioral performance and no differences were observed in brain activity or connectivity patterns within the amygdalae or r-ACC. Decreased fractional anisotropy values were noted, however, for the bilateral superior longitudinal fasciculi and posterior cingulate cortex. We interpret these findings to suggest that emotional valence determination and non-verbal skill sets are largely intact at this stage of the disease, but signs foreshadowing future decline were revealed by possible white matter deterioration. Understanding how non-verbal skill sets are altered, while remaining largely intact, offers new insights into how non-verbal communication may be more successfully implemented in the care of AD patients and highlights the potential role of DTI as a presymptomatic biomarker.